2016
DOI: 10.5194/acp-16-8309-2016
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary aerosols in Beijing in winter: sources, variations and processes

Abstract: Abstract. Winter has the worst air pollution of the year in the megacity of Beijing. Despite extensive winter studies in recent years, our knowledge of the sources, formation mechanisms and evolution of aerosol particles is not complete. Here we have a comprehensive characterization of the sources, variations and processes of submicron aerosols that were measured by an Aerodyne high-resolution aerosol mass spectrometer from 17 December 2013 to 17 January 2014 along with offline filter analysis by gas chromatog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

86
300
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 326 publications
(409 citation statements)
references
References 99 publications
(188 reference statements)
86
300
9
Order By: Relevance
“…The average O/C ratio calculated based on the AMS PM1 measurements and updated calibrations by 5 Canagaratna et al (2015) is 0.4 ± 0.1 (Fig. S11), similar to values reported previously in winter Beijing Sun et al, 2016). The effect of liquid-liquid phase separation on particle pH remains unclear.…”
Section: Assumptions and Limitations Of Thermodynamic Modelingsupporting
confidence: 69%
See 3 more Smart Citations
“…The average O/C ratio calculated based on the AMS PM1 measurements and updated calibrations by 5 Canagaratna et al (2015) is 0.4 ± 0.1 (Fig. S11), similar to values reported previously in winter Beijing Sun et al, 2016). The effect of liquid-liquid phase separation on particle pH remains unclear.…”
Section: Assumptions and Limitations Of Thermodynamic Modelingsupporting
confidence: 69%
“…Synoptic weather patterns are dominated by the Siberian high-pressure system (Jia et al, 2015), under which the northerly winds bring dry and clean air into this region with ambient RH often dropping to as low as about 20% (when aerosol particles are most likely solid). When the northerly winds slacken, often occurring during 25 the NCP winter haze events, the atmospheric conditions are characterized by stagnant inversion, weak southerly winds, and rapid accumulation of both air pollutants and water vapor, and the ambient RH often reaches 80-90% (when aerosol particles are most likely liquid) (Zheng et al, 2015;Tie et al, 2017;Sun et al, 2016;Gao et al, 2016;Yin et al, 2017). Recent field measurements of PM1 in winter Beijing by Liu et al (2017b) suggested that the phase state of particles was sensitive to ambient RH and that there existed a gradual transition from semisolid at RH of about 20% to liquid at RH of 30 about 60%.…”
Section: Ph Prediction By Thermodynamic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more detailed description of the operations and calibrations of this HR-AMS can be found in Xu et al (2015) and Sun et al (2016). Other collocated measurements in two containers at ground level included gaseous species of O 3 (TEI 49C UV absorption analyzer), NO (TEI 42i TL NO analyzer), and NO 2 (CAPS NO 2 monitor, Aerodyne Research Inc.) and size-resolved particle number concentrations (11-550 nm) by a scanning mobility particle sizer (SMPS) equipped with a long differential mobility analyzer (DMA, TSI, 3081A) and a condensation particle counter (CPC, TSI, 3772).…”
Section: Collocated Measurementsmentioning
confidence: 99%